Development of Android CHEMDIC Mobile Learning to Prevent Student Misconceptions on Periodic System of Elements Material - Rahmadhani, Muhammad Zidan; Sukarmin, Sukarmin (Jurnal Pijar Mipa, 2024)
Chemistry is a multidimensional discipline that contains concepts from simple to complex and concrete to abstract. This makes it difficult for students to understand chemistry and causes a lot of misconceptions. Facts in the field show that only some students understand the concept of the periodic system of elements. In preliminary research, mobile learning has been studied and can improve the effectiveness of individual learning for students anywhere and anytime. This study aims to determine the feasibility of CHEMDIC mobile learning in preventing student misconceptions in the context of the periodic system of elements. This feasibility is reviewed based on the validity and practicality of mobile learning in preventing student misconceptions. The methodology in this study is Research and Development (R&D) using the 4D development model proposed by Thiagarajan with the following stages: define, design, develop, and disseminate. However, this research is limited only to the development stage due to several considerations such as time, effort, and facilities. The limited trial was carried out with 15 students of SMAN 1 Krian Sidoarjo who had obtained learning materials in the context of the periodic system of elements and were selected based on the largest number of students who were included in the category of not understanding concepts based on the results of the pretest. CHEMDIC mobile learning is declared valid if it fulfils the minimum mode score of 4, while it is stated as practical if it fulfils the minimum percentage of ≥61%. This research shows the results of the validity of CHEMDIC mobile learning with the acquisition of content validity mode scores of 5 with a very valid category and a construct validity mode score of 4 with a valid category. Then, practicality, with the acquisition of a percentage in the student response questionnaire of 96%, was in the very practical category. This result shows that android CHEMDIC mobile learning is feasible to prevent students' misconceptions about the material of the periodic system of elements.